Problem Analysis of Hydraulic Accumulators on Airbus A320 Aircraft - Silaban, Divasco Togap; Yusuf, Yusvardi (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2023)
This study investigated the hydraulic system on Airbus A320 aircraft, focusing on the problems that often occur with hydraulic accumulators as well as the maintenance steps required. The Airbus A320 hydraulic system consists of three main systems, namely the Green, Yellow, and Blue hydraulic systems, which play an important role in the operation of vital systems in the aircraft. Periodic checks of nitrogen pressure in hydraulic power accumulators, in accordance with AMM guidelines, are key in preventing hydraulic system problems. Common hydraulic accumulator problems, such as hydraulic leaks, pressure drops, and internal leaks, are often caused by insufficient prefill pressure or too high a fill pressure. Necessary maintenance measures include pressure checks in accordance with AMM standards and pressure adjustments if required. By understanding common hydraulic accumulator problems and their maintenance, aircraft technicians can maintain hydraulic system performance in optimal conditions, ensuring the safety and optimal performance of the aircraft during operation.